APLIKASI MOBILE DARURAT BENCANA PADA KABUPATEN MUSI BANYUASIN - Megawaty, Megawaty ; Bakti, Ahmad Mutatkin; Permana, Hikmat (JURNAL ILMIAH MATRIK, 2017)
Currently BPBD Kabupaten Musi Banyuasin not yet available information system that manage data access specially in the form of disaster location information so that when BPBD Kabupaten Musi Banyuasin or society will do prevention or rescue effort do not have high information accuracy. This research makes mobile based application for information of disaster prone area in Musi Banyuasin Regency. The benefits can provide an alternatif information dissemination related to the location information of natural disasters, especially floods and landslides in Musi Banyuasin Regency, can provide fast, accurate and accurate data for the Quick Response Team for Disaster Response located in the field according to the location of natural disasters, especially floods and landslides in Regency of Musi Banyuasin. The research method used descriptive method while software development using Mobile-D method. The stages are explor, initialize, productionize, stabilize, system test and fix. Keywords: Application, Mobile, Disaster